THE INDONESIAN GOVERNMENT’S ROLE IN COMBATING HUMAN TRAFFICKING IN INDONESIA (CASE STUDY 2014-2019) - Advenita, Victoria; Susilawati, Ningsih; Kurnadi, Andrea (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2020)
Based on the fluctuating trend of human trafficking cases which is considered as still high in number, the Government of Indonesia should take serious action in combating these issues in Indonesia to protect the human rights of Indonesian citizens. The human security issue and actions taken by the Government of Indonesia will be the fundamental objective of this research. The theoretical framework used to analyze the issue in this study is the theory of Human Security, Role Theory, and the concept of Human Trafficking. To analyze the data, this study will use qualitative methods. The results show that the government has succeeded in managing several steps that are useful to increase awareness in cooperation and coordination between state institutions. The government has also kept the cooperation well with several foreign states and external parties to eradicate human trafficking not only in Indonesia but also in the international sphere.